Berkhotbah Secara Online Sebagai Praktik Spiritual:Studi Kualitatif Penghayatan Hamba Tuhan di Beberapa Gereja di Bandung - Dedi Gunawan (Sekolah Tinggi Teologi Bandung, 2024)
This article aims to examine the shifting impact of conventional preaching to online preaching during the pandemic on the preacher's understanding of online preaching as a spiritual practice. Using phenomenology, a qualitative method, the researchers explored how online preaching experiences of five pastors in three different churches in Bandung affected their understanding of online preaching as a spiritual practice. The results indicate that the respondents adapted to online preaching because of the awareness of the congregation's need to hear God's Word during the pandemic. Respondents also maintain the biblical meaning of preaching as sacred preaching, conveying the message of the living God and applicable. Respondents experience spiritual experiences in online preaching. Respondents found advantages and disadvantages to online preaching, namely being able to reach listeners extensively and intensively, but it depends on unstable technology and is limited in personal ministry. The results of this study will help churches, seminaries, and preaching scholars in equipping God's servants to be better preachers of the living Word of God.